Quantum Imaging Techniques for Early Diagnosis of Neurological Disorders - Abdullah, Diana Noori Yousif; Yassin, Rahma Talal Taha; Aliwy, Shimaa Ali Younes; Ali, Amenh Ali Hassan; Shihab, Samar Abbas (American Journal of Botany and Bioengineering, 2025)
Quantum imaging has emerged as a revolutionary approach in the early diagnosis of neurological disorders, offering enhanced sensitivity and resolution compared to conventional imaging techniques. Despite advancements in medical imaging, early detection remains challenging due to the complexity of neurological conditions and the limitations of current diagnostic tools. This study addresses the knowledge gap by exploring the principles of quantum imaging and its applications in detecting neurodegenerative diseases. A qualitative analysis of recent research and case studies was conducted to assess the effectiveness of quantum imaging techniques. Findings indicate that quantum-enhanced imaging methods, such as quantum entanglement and ghost imaging, significantly improve diagnostic accuracy by providing non-invasive, high-contrast, and real-time visualization of neural structures. These results highlight the potential of quantum imaging in transforming neurological diagnostics, leading to earlier interventions and improved patient outcomes. Further research is needed to integrate quantum imaging into clinical practice and establish standardized protocols for its widespread adoption.